Interlimb Coordination and Auditory-Motor Synchronization in Children with Developmental Coordination Disorder: Examining Antiphase Knee Movements with Auditory Metronomes While Seated - Mieke Goetschalckx; Lousin Moumdjian; Eugene Rameckers; Peter Feys (MDPI AG, 2024)
Background: Children with developmental coordination disorder (DCD) exhibit reduced interlimb coordination compared to typically developing children (TDC) during complex tasks like running, which requires dynamic postural control. However, the extent of interlimb coordination difficulties in DCD during tasks that demand minimal dynamic balance, such as self-paced and externally auditory-paced tasks, remains unclear. This study aimed to compare interlimb coordination and auditory-motor synchronization between children with DCD and TDC during a seated antiphase coordination task of the lower limbs, which has minimal postural control requirements. Methods: Twenty-one children with DCD and 22 TDC performed an antiphase knee flexion and extension task while seated, in three conditions (baseline silence, metronome discrete, and metronome continuous), for three minutes. The interlimb coordination, synchronization, and spatiotemporal movement parameters were analyzed using a mixed model analysis; Results: Children with DCD displayed less coordinated interlimb movements compared to TDC (p = 0.0140), which was the result of the greater variability in coordinating antiphase knee flexion-extension movements (p < 0.0001). No group differences in spatiotemporal movement parameters were observed. Children with DCD, compared to TDC, had a lower synchronization consistency to metronomes (p = 0.0155). Discrete metronomes enhanced interlimb coordination compared to the baseline silence condition (p = 0.0046); Conclusions: The study highlights an inferior interlimb coordination and auditory-motor synchronization in children with DCD compared to TDC. Implementing metronomes with a discrete temporal structure improved the interlimb coordination of both groups during the used fundamental seated interlimb coordination task, supporting theorical frameworks of event-based timing.